The Achievements and Challenges of Silicon Photonics. (3rd June 2008) - Soref, Richard
Abstract : A brief overview of silicon photonics is given here in order to provide a context for invited and contributed papers in this special issue. Recent progress on silicon-based photonic components, photonic integrated circuits, and optoelectronic integrated circuits is surveyed. Present and potential applications are identified along with the scientific and engineering challenges that must be met in order to actualize applications. Some on-going government-sponsored projects in silicon optoelectronics are also described.